Preparation of polymeric carbon nitride/TiO2 heterostructure with NH4Cl as template: Structural and photocatalytic studies. (May 2022) - Wu, Zhengjie; Zhao, Youhai; Chen, Xiong; Guo, Yongxiang; Wang, Haiwang; Jin, Yaran; He, Ping; Wei, Qingquan; Wang, Bingzhu
Abstract: In this paper, a method for preparing polymeric carbon nitride/TiO2 (PCN/TiO2 ) with NH4 Cl as template is proposed. Comparing with PCN prepared with conventional methods, the specific surface area of PCN/TiO2 is higher, which also improves the photocatalytic performance. The structure and evolution of samples were explored via FT-IR, XRD, SEM, TEM, BET and XPS in order to analyze the reaction mechanism of PCN/TiO2 . In the meantime, the electron-hole separation efficiency and energy band structure were explored by PL and UV–Vis spectra. In addition, the RhB degradation mechanism and electrons-holes transport path of PCN/TiO2 was analyzed by degradation experiments and EPR. The results show that the NH4 Cl which is the template was decomposed after calcination, therefore PCN showed the porous morphology. The compound of PCN and TiO2 formed heterojunction, which can effectively promote the electron-hole separation rate to improve the photocatalytic efficiency. The PCN/TiO2 (2.5:1) was found to have the best dye degradation efficiency and the degradation rate of RhB could reach 83.81% within 150 min. During the degradation of RhB, the active substances are h +, ∙OH and · O 2 − and the mechanism of electron-hole transmission is Type-Z transport mechanism. Graphical abstract: Image 1 Highlights: During the calcination process, the NH4 Cl template is easier to remove and the specific surface area of PCN is increased. The rate of PCN/TiO2 photocatalytic degradation of RhB is equivalent to 8.26 times that of pure PCN. The degrading active substances are h +, ∙OH and · O 2 −, and the electron-hole transport mechanism is Type-Z mechanism.